A consonância entre projetos pedagógicos e a realidade do entorno social de escolas públicas da Zona Norte de São Paulo: uma análise e algumas considerações - Brossi-Monteiro, Karina Pellegrino (2012)
This work it is a document analisys that adresses a study of the Pedagogical Projects of two schools located in the northern city of São Paulo, namely in the districts of Jaçanã and Tucuruvi respectively, and the way they were planed according to reality of the communities where they operate. The objective of this research is to conduct a study on educational projects, analyzing their composition, whether they are the result of a collective work, and especially considering the data from the social context and reality of the school community and also provide service to and exchange with community in implementing the actions proposed in order to show the differences between the schools studied, as well as their locations. For this purpose, specific objectives involved delimited to verify a diagnosis was made on the specific community school, and analyze the educational project was developed on basis of their specific local idiosyncrasies, noting the characteristics that the school has and how the project characterizes. For this was done reading the educational projects of the selected schools, whose data collected as specific script, we analyzed about axes created as the data collected to help us check the consonances and dissonances of ideas and action plans contained in the projects of schools. The analysis was supported by authors of theoretical sociology of education, education and social services, such as Apple & Beane (2001), Young (2001), Gimeno Sacristan (1998), Azanha (2006), Veiga (1995), Haydt (1997), Sposati (1996; 2000), Saviani (1976) and Albuquerque (2005), so it was verified that the selected districts first (Jaçanã) presents data showing lower levels of quality than the second district (Tucuruvi). The projects for their respective schools, in turn, were consistent with the reality of their communities. While the school located in Jacana has no structure or an appropriate plan of action that makes possible the improvement of regional school located in Tucuruvi has a well-designed project, with a diagnosis that is consistent with the priorities established by the same according to their conceptions